Elevated Soluble Fms-Like Tyrosine Kinase-1 and Placental-Like Growth Factor Levels Are Associated With Development and Mortality Risk in Heart Failure. (January 2016) - Hammadah, Muhammad; Georgiopoulou, Vasiliki V.; Kalogeropoulos, Andreas P.; Weber, Malory; Wang, Xi; Samara, Michael A.; Wu, Yuping; Butler, Javed; Tang, W.H. Wilson
Abstract : Background—: Vascular endothelial dysfunction may play an important role in the progression of heart failure (HF). We hypothesize that elevated levels of vascular markers, placental-like growth factor, and soluble Fms-like tyrosine kinase-1 (sFlt-1) are associated with adverse outcomes in patients with HF. We also assessed possible triggers of sFlt-1 elevation in animal HF models. Methods and Results—: We measured plasma placental-like growth factor and sFlt-1 in 791 HF patients undergoing elective coronary angiogram. Median (interquartile range) placental-like growth factor and sFlt-1 levels were 24 (20–29) and 382 (277–953) pg/mL, respectively. After 5 years of follow-up, and after using receiver operator characteristic curves to determine optimal cutoffs, high levels of sFlt-1 (≥280 pg/mL; adjusted hazard ratio, 1.47; 95% confidence interval, 1.03–2.09; P =0.035) but not placental-like growth factor (≥25 pg/mL; adjusted hazard ratio, 1.26; 95% confidence interval, 0.94–1.71, P =0.12) were associated with adverse cardiovascular outcomes. In addition, significant elevation of sFlt-1 levels was observed in left anterior descending artery ligation and transverse aortic constriction HF mouse models after 4 and 8 weeks of follow-up, suggesting vascular stress and ischemia as triggers for sFlt-1 elevation in HF. Conclusions—: Circulating sFlt-1 is generated as a result of myocardial injury and subsequent HF development. Elevated levels of sFlt-1 are associated with adverse outcomes in stable patients with HF. Abstract : Supplemental Digital Content is available in the text.